If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + (p + -6) + (p + 60) + 3(p + -53) = 120 Reorder the terms: p + (-6 + p) + (p + 60) + 3(p + -53) = 120 Remove parenthesis around (-6 + p) p + -6 + p + (p + 60) + 3(p + -53) = 120 Reorder the terms: p + -6 + p + (60 + p) + 3(p + -53) = 120 Remove parenthesis around (60 + p) p + -6 + p + 60 + p + 3(p + -53) = 120 Reorder the terms: p + -6 + p + 60 + p + 3(-53 + p) = 120 p + -6 + p + 60 + p + (-53 * 3 + p * 3) = 120 p + -6 + p + 60 + p + (-159 + 3p) = 120 Reorder the terms: -6 + 60 + -159 + p + p + p + 3p = 120 Combine like terms: -6 + 60 = 54 54 + -159 + p + p + p + 3p = 120 Combine like terms: 54 + -159 = -105 -105 + p + p + p + 3p = 120 Combine like terms: p + p = 2p -105 + 2p + p + 3p = 120 Combine like terms: 2p + p = 3p -105 + 3p + 3p = 120 Combine like terms: 3p + 3p = 6p -105 + 6p = 120 Solving -105 + 6p = 120 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '105' to each side of the equation. -105 + 105 + 6p = 120 + 105 Combine like terms: -105 + 105 = 0 0 + 6p = 120 + 105 6p = 120 + 105 Combine like terms: 120 + 105 = 225 6p = 225 Divide each side by '6'. p = 37.5 Simplifying p = 37.5
| p(x)=4x^3-6x^2-2x+9findp(0) | | r=my | | (X+4)(x-4)(x-2)=4 | | 4x-y=8fory | | -8(p-15)=224 | | 10+3(4-6a)=-1(6a+12) | | -5x^2-9+10x+8x^2-13x= | | 13-4(2x+3y)= | | 167+19x+16=1132 | | 5x+3x=2x+12 | | 1/4(5x-16) | | X-2a=9 | | 2x+84=8x+6 | | 4t+3+3t-6t=3+5 | | 5p/5=1 | | x^2-32x+81=0 | | -c=-1/3 | | 11/12x6/7 | | 2(n-3)=4m+1 | | -5(9x+3)= | | 3x+29/5+x+22/4=13 | | 430+n/4=150 | | X^6+56x-512=0 | | -9x^2+4+10x^2-6x= | | 7(x-5)=3x+9 | | 10x^2-9+5x-8x^2-11= | | 42x=42x-42 | | 2(4y-5)+7=-1 | | 6x=x+1.5 | | -14x^2-6x+21x-9=0 | | 2r+4=3r-2(r-4) | | -750=30x |